Sintesis Karbon Aktif dari Tandan Kosong Kelapa Sawit (TKKS)/ZnO Terdeposisi pada Polistirena untuk Mereduksi Kadar Besi (Fe) dalam Air Gambut - Apriyani, Nanda Ayu; Nurhanisa, Mega; Wahyuni, Dwiria (UNIB Press, 2026)
Peat water contains iron (Fe) levels exceeding health standards, causing a brownish color, metallic odor, and adverse health effects. This study aims to reduce Fe levels in peat water using a composite of activated carbon (AC) from oil palm empty fruit bunches (EFB), zinc oxide (ZnO), and polystyrene (PS). Activated carbon synthesis was conducted through physical activation using microwaves at 600 watts for 15 minutes. ZnO is suggested to act as a photocatalyst enhancing adsorption performance and enhance Fe adsorption efficiency, while PS acts as a binder for the composite. The effectiveness was tested with ZnO concentrations of 10%, 15%, 20%, and 25%, with contact times of 2, 4, and 6 hours. The highest Fe reduction was achieved at a ZnO concentration of 25% with a 4-hour contact time, reducing Fe levels by 74.01%. However, at a 6-hour contact time, the adsorption efficiency decreased due to saturation and potential desorption. These findings indicate that the KA/ZnO/PS composite is a promising adsorbent material for peat water treatment